Kidney Function and Disability‐Free Survival in Older Women. Issue 1 (21st September 2016) - Cavanaugh, Alyson M.; LaCroix, Andrea Z.; Kritz‐Silverstein, Donna; Rillamas‐Sun, Eileen; Rifkin, Dena E.
Abstract : Objectives: To examine the prospective association between kidney function and three outcomes: survival to age 85 with functional independence, survival to age 85 with disability, and death before age 85. Design: Prospective study. Setting: Women's Health Initiative, conducted at 40 U.S. clinical centers. Participants: Postmenopausal women enrolled between 1993 and 1998 with baseline biomarker assessments who had the potential to reach age 85 before September 2013 (N = 7, 178). Measurements: Kidney function was measured according to estimated glomerular filtration rate (eGFR) calculated from serum creatinine collected at baseline. Outcomes were survival to age 85 with functional independence, survival with disability, or death before age 85. Disability was defined as mobility or activity of daily living limitations measured by questionnaire. Results: eGFR was greater than 90 mL/min per 1.73 m 2 in 22.7% of women, 60 to 89 mL/min per 1.73 m 2 in 66.5%, 45 to 59 mL/min per 1.73 m 2 in 8.7%, and less than 45 mL/min per 1.73 m 2 in 2.0%. Median follow‐up was 15 years. Of 4, 953 survivors, 3, 155 reported no physical disability at age 85. Two thousand two hundred twenty‐five participants died before age 85. Women with an eGFR of 90 mL/min per 1.73 m 2 or greater had 2.71 times greater odds of survival to age 85 with functional independence than of dying before 85 (95% confidence interval (CI) = 1.62–4.51) than those with an eGFR less than 45 mL/min per 1.73 m 2, women with an eGFR of 60 to 89 mL/min per 1.73 m 2 had 3.04 times (95% CI = 1.85–5.00) greater odds, and women with an eGFR of 45 to 59 mL/min per 1.73 m 2 had 2.22 times (95% CI = 1.31–3.76) greater odds. Similar, but slightly weaker odds were seen for survival to age 85 with disability. Better kidney function was not significantly associated with greater likelihood of survival to age 85 with independent function than of surviving with disability. Conclusion: Better kidney function was associated with greater likelihood of survival to age 85 with and without disability.